Astralis : Espace culturel Louis Vuitton. - Pique, Pascal; Méheust, Bertrand; Ransford, Emmanuel (Paris : Espace culturel Louis Vuitton, 2014)
Altmejd, David ; Sæthre, Børre ; Piene, Chloe ; Favéro, Jean-Luc ; Case, Charley ; Gastaldon, Vidya , Basserode ; Hapaska, Siobhán ; Deroubaix, Damien ; Mechita, Myriam ; Banerjee, Rina ; Art Orienté Objet ; Méheust, Bertrand ; Ransford, Emmanuel
Astralis, Espace culturel Louis Vuitton, Paris, 7 février - 11 mai 2014
boek